Peran mediasi budaya perusahaan inovatif terhadap strategi peningkatan kinerja karyawan - Gumara, Reza Yudha; Yanuar, Yanuar (Jurnal Manajemen Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the influence of Employee Engagement, Employee Value Proposition (EVP), and Talent Management Practices on Employee Performance with Innovative Corporate Culture as a mediating variable. The research was conducted on permanent and active employees at XYZ Company using a quantitative approach and a survey method through electronic questionnaires. A total of 242 respondents were selected using the Simple Random Sampling technique. Data were collected from January to February 2025. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0 software. The results indicate that Employee Engagement has a significant effect on Innovative Corporate Culture, while Employee Value Proposition and Talent Management Practices do not have a significant effect on Employee Performance. Additionally, Innovative Corporate Culture does not significantly mediate the relationship between Employee Engagement and Employee Performance. Penelitian ini bertujuan untuk menganalisis pengaruh Employee Engagement, Employee Value Proposition (EVP), dan Talent Management Practices terhadap Employee Performance dengan Innovative Corporate Culture sebagai variabel mediasi. Penelitian dilakukan terhadap karyawan tetap dan aktif di Perusahaan XYZ dengan menggunakan pendekatan kuantitatif dan metode survei melalui kuesioner elektronik. Sampel yang digunakan sebanyak 242 responden yang diperoleh dengan teknik Simple Random Sampling. Data dikumpulkan pada Januari sampai dengan Februari 2025. Pengolahan data dilakukan dengan metode Partial Least Squares Structural Equation Modeling (PLS-SEM) menggunakan aplikasi SmartPLS 4.0. Hasil penelitian menunjukan bahwa Employee Engagement memberikan pengaruh yang signifikan terhadap Innovative Corporate Culture, sedangkan Employee Value Proposition dan Talent Management Practice tidak berpengaruh signifikan terhadap Employee Performance, serta Innovative Corporate Culture tidak signifikan untuk memberikan mediasi Employee Engagement terhadap Employee Performance.